Gender representation in Filipino storybooks for children - Mante-Estacio, MA. Joahna; Dumalay, Fernand Kevin; Rentillo, Philip (Universitas Pendidikan Indonesia, 2018)
Aside from learning values, traditions, and significant experiences from storybooks, children also learn about their roles as males and females from these learning materials. Previous studies on gender representation revealed that male characters in children’s storybooks are given more active roles through the verbs assigned to them. The present study examines gender portrayal in bilingual children’s literature written by Filipino authors. Using word count guided by the verb taxonomy of Johnson and Young (2002), 60 award winning and non-award winning books published between 2006 to 2017 were analyzed. Overall, the results reveal that the male characters continue to be assigned more active roles in the stories; however, they can also be assigned to roles that were traditionally given to female characters. Furthermore, both male and female names follow a two-syllabic structure which underlies the hypothesis that they are easily remembered by young readers. The implications of these findings in critical literacy are further discussed.